CONSERVATION OF STRAWBERRY (Fragaria x ananassa Duch cv. Camarosa) BY EDIBLE COATING APPLICATION OF SABILA GEL MUCILAGE (Aloe barbadensis Miller) AND CARNAUBA WAX - RESTREPO F., Jorge I.; ARISTIZÁBAL T, Iván D. (Vitae, 2010)
The strawberry is a well accepted fruit by consumers. Its culture presents a significant yield in all months of the year and enjoys a good price positioning. The objective of this study was to extend the strawberry (Fragaria x ananassa Duch cv. Camarosa) shelf life by applying two edible coatings developed from the Aloe vera (Aloe barbadensis Miller) mucilaginous gel and carnauba wax. From the results obtained it was concluded that the use of edible coatings from Aloe vera mucilaginous gel and carnauba wax led to an increase of at least ten days in the strawberry shelf life, with reduced moisture loss and respiration rate. Besides, conservation of firmness without showing noticeable changes in color was observed, in comparison to the fruits used as a control.